PREVALENCE OF HEPATITIS C VIRUS ANTIBODY AMONG UNDERGRADUATES IN OGBOMOSO, SOUTH-WESTERN NIGERIA - Jemilohun, Abiodun Christopher; Oyelade, Bolaji Oyetunde; Oiwoh, Sebastine Oseghae (African Journal of Infectious Diseases (AJID), 2014)
Background: This study was conducted to determine the prevalence of hepatitis C virus antibody (anti-HCV), among a healthy university undergraduate population in south-western Nigeria.Materials and Methods: Relevant medical information of students who underwent the post-admission screening exercise for the year 2012, at the Ladoke Akintola University of Technology (LAUTECH), Health Center, Ogbomoso were extracted from the laboratory log book. All tests were done using rapid anti-HCV test kit by Health - Chem diagnostics, USA. A total of 1,572 students were included in the study. The mean age was 19.61 (± 2.75) years while the age range was 15- 50 years. A total of 821 (52.20%), of the subjects were males while 751 (47.80%) were females. More than ninety nine percent (99.90%) of the subjects were aged 15-30 years, whereas those aged ≥31 years were comparatively few (0.60%). Results: Of the 1572 students, 6 tested positive, giving an overall prevalence of 0.40%. Three (0.37%) of the 821 male subjects tested positive while 3(0.40%) also of the 751 female subjects tested positive. Age-group 21-30 years had the highest prevalence of anti - HCV (0.50%), followed by age-groups ≤ 20 years with 0.30% prevalence. None of the subjects in age-groups 31-40 and ≥ 41 years tested positive.Conclusion: These observed differences were not statistically significant. The prevalence of Hepatitis C Virus is low among the young healthy undergraduate population in the south - western region of Nigeria.